Pengaruh Media Pembelajaran Kartu Domino Terhadap Hasil Belajar pada Materi Struktur dan Fungsi 2023/2024 Tumbuhan Kelas IV SD Negeri 101928 2023/2024 Rantau Panjang - Sinaga, Usfuri Amelia Putri; Safitri, Layil; Hariati, Emy (Medan Resource Center, 2024)
This study aims to investigate the influence of domino card learning media on student outcomes in the subject of plant structure and function in fourth-grade students at SD Negeri 101928 Rantau Panjang. The research explores two main objectives: (1) to measure the impact of using domino card media on student learning outcomes, and (2) to assess overall student performance in the given material. A quasi-experimental quantitative approach was applied, involving two groups: an experimental class and a control class, each consisting of 20 students. Pretest and posttest evaluations were conducted to compare the learning outcomes. The findings indicate that the experimental group, which used domino card media, achieved a higher average score of 92, compared to the control group’s highest score of 88, demonstrating a significant positive effect of the learning media on students' science learning outcomes.